(3GdGfJUGa ef GdcTGas - (3CMeO Hf eMeO Hf efUhQ GdEScfOQGfj , fGUQ GdOjf CHj GdYHGS , GdeYQha HGHf GdefjQ , J (B683 (3g`s
(3BNQgG (B:s
(3aZGjI LOd GdHjGf hQjO GddSGf HJcQGQ WGgQ s
(3GdcTGa ddReNTQi GfXQ cTa GdXfhf L(B2 (3U` (B147s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs